LEARNING READING SKILLS: PROBLEMS AND SOLUTIONS - Cicilia Ovavia; Elfia Sukma (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Reading as a literacy activity is a key to advancing education. Learning to read becomes crucial at elementary schools in order to increase students' language skills which support other learning. Based on the results of interviews and observations, there was a problem that in learning Bahasa Indonesia at elementary schools, thestudents' reading skills were low because the teacher only used the lecture method and books as a guide for students in reading skills. As a result, students were lazy to read and to understand the information contained in the books. This study was conducted to find out problems teachers and students faced in reading lessons at elementary schools. This study used qualitative descriptive research involving grade III students of SDN 08 Mandeh. The informants were selected by using the snowball sampling technique. This study prioritized direct data from informants and observations made in the field. The object of this study was the students’ reading skills in learning Bahasa Indonesia at elementary schools. The data in the study were collected through observation, interviews and documentation. Based on the data from observations, interviews and documentation, the researchers obtained solutions to the problems found in Reading Skills. The solutions were using attractive learning media, appropriate learning models, choosing various reading materials, providing motivation and feedback, and encouragement from parents.